Students’ Perspectives on Gender Inclusive Practices in Teacher Education Graduate Programs of a Nepali University (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
Gender inclusion is a part of the course in the teachers’ education program, which helps to understand the contemporary issues and problems through the lens of gender for the development and betterment of society. Gender inclusion ensures equality in the curriculum. This study explores gender-inclusive practices from the students’ perspective in the Masters in education courses of Kathmandu University School of Education. The study aims to identify the status of the inclusion of gender in curriculum content, pedagogical practices, assessment and research activities, and organizational provisions from students’ perspectives in the curriculum. The data were collected from the 2016 to 2019 batch of students from three different graduate programs through surveys, interviews, and focus group discussions. The data was analyzed to describe the current situation of gender inclusion in content, pedagogy, assessment and research and organizational provisions. The study concluded by emphasizing the urgency of mindful actions in the integration of gender. Even though there are discussions regarding gender in very few courses, the students felt that those discussions were inadequate. The students opined that the faculty members should bring gender discussion in the classroom as well as in larger academic discourse to contribute toward gender responsiveness as an individual and from institutional both.